New Report: Helopeltis cinchonae Mann (Hemiptera: Miridae) Attacking Commercial Hydrangea Flowering Plants in East Java, Indonesia - Suputa, Suputa; Sari, Riya Fatma; Tarno, Hagus (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
Formerly, the mirid bug has not been recorded for Hydrangea macrophylla (Thunb.), in Indonesia. Infestation of mirid bug was found on the leaves of Hydrangea in the vegetative growth phase from July 2023 to July 2024 in five hamlet fields at the ornamental farming center in Batu City, East Java. Plant samples were observed diagonally and five plants in each point were selected for samples. On each of the top ten leaves of the sample plants, the percentage of attack symptoms was carefully observed. Nymphs found during the observation were reared to imago, and adults were identified as Helopeltis cinchonae Mann (Hemiptera: Miridae). Insect pests, infestation symptoms, and egg locations were documented during the study. This is the first report of a pest causing significant damage to commercial Hydrangea plants in Batu, East Java, indicating the need to develop an integrated pest management strategy to support increased Hydrangea cut flower production in Batu.